Infrastructure finance in developing countries: An overview - Antonio Estache (EIB Papers, 2010)
This study analyzes the main approaches to infrastructure financing in developing countries and their evolution. It places the discussion in the context of the importance of infrastructure investment and maintenance needs to achieve growth and broader social objectives. It summarizes the evidence on the efficiency, equity and fiscal consequences of the main public and private financing options commonly used to achieve these goals in these countries. It shows the limits of the role of the private sector as a source of financing of infrastructure and the wide underestimation of public-sector financing support needed to serve the poorest and ensure that services are offered at prices consistent with their ability to pay. It concludes with forward-looking lessons from roughly 20 years of efforts to diversify the sources of infrastructure finance in developing countries.
Keywords: 330